THE TRANSFORMATION OF VALUES AND KNOWLEDGE IN THE YELLOW BOOK AT DAYAH DARUSSALAM LAMPOH TUAH GRONG GRONG IN THE DIGITAL AGE - Daysra abrar Daysra abrar; Salami mahmud; Nurbayani Ali (STAI Nusantara Kota Banda Aceh, 2026)
This study investigates the transformation process of Islamic knowledge and values within Kitab Kuning learning at Dayah Darussalam Lampoh Tuah Grong Grong, focusing on how traditional Islamic educational institutions in Aceh navigate the digital age while maintaining their academic rigor and spiritual core. Across most dayah in Aceh, students are prohibited from using mobile phones, while digital technology access remains limited to educators (asatidz), religious scholars (teungku), and advanced students for educational, administrative, or instructional purposes. Employing a descriptive-qualitative approach supported by fieldwork observations and interviews, this study reveals that digital transformation in dayah education unfolds selectively and value-driven. Technology serves as a supplementary pedagogical resource for teachers rather than a central learning platform for students. Conventional instructional methods including halaqah (study circles), boh bareh (diacritical marking), syarah (interpretive exposition), and muthala'ah (self-directed reading) remain the cornerstone of knowledge transmission. Concurrently, digital instruments are utilized to enhance reference materials, boost efficiency, and support educators in content delivery. The restriction on mobile phone usage among students contributes to maintaining discipline, focus, and reverence for knowledge, fostering deep intellectual and spiritual development. Thus, the evolution of Kitab Kuning education within the digital landscape represents an ethical modernization approach—rooted in Islamic moral principles, humility, and the pursuit of blessed knowledge (barakah al-'ilm). This framework demonstrates the endurance and ongoing significance of Aceh's dayah institutions as custodians of classical Islamic learning amid swift global technological advancement.